DIRECT ETHOXYLATION OF GLYCEROL MONO OLEATE FROM PALM OIL DERIVATE AS A NOVEL NON-IONIC POLYMERIC SURFACTANT - Joddy Arya Laksmono; Indri Badria Adilina; Egi Agustian (Dept. of Chemical Engineering, Diponegoro University, 2008)
The work investigates ethoxylation of glycerol mono oleate (GMO) performed in the presence of an alkaline catalyst. Glycerol mono oleate applied was derivated from Indonesian palm oil. The reaction was conducted with variation of Glycerol mono oleate : ethylene oxide ratio, temperature, and catalyst concentration. Forier Transform Infra Red (FTIR) and Nuclear Magnetic Resonance (NMR) analysis showed products with degrees of ethoxylation n=2 and n=3. FTIR analysis of products gave a new peak at 1570 cm-1 supporting that C-O-C bond was formed. New peaks were also observed in 13-C-NMR analysis of run 2 and run 3 with chemical shift of (δ) 61.3385; 61.9108; 62.5117; 63.8566; 66.0982; 72.6127 and 61.2172; 63.2393; 65.9100; 72.5201, respectively. Glycerol mono oleate ethoxylated was yielded and could be useful for a novel non-ionic polymeric surfactant.